A Decade of Time Series Sampling Reveals Thermal Variation and Shifts in Pseudo-nitzschia Species Composition That Contribute to Harmful Algal Blooms in an Eastern US Estuary - Roche, Katherine M.; Sterling, Alexa R.; Rynearson, Tatiana A.; Bertin, Matthew J.; Jenkins, Bethany D. (Frontiers in Marine Science, 2022)
In 2016-17, shellfish harvesting closed for the first time in Narragansett Bay, Rhode Island, USA, from domoic acid (DA), a neurotoxin produced by diatoms of the Pseudo-nitzschia genus. Pseudo-nitzschia have occurred frequently for over 60 years in Narragansett Bay’s Long-Term Plankton Time Series (NBPTS), therefore it is surprising that the first closure only recently occurred. Pseudo-nitzschia species are known to vary in their toxin production, thus species identification is critical for understanding the underlying ecological causes of these harmful algal blooms (HABs). DNA in plankton biomass can be preserved for many years, so molecular barcoding of archived samples is useful for delineation of taxa over time. This study used amplification of the Pseudo-nitzschia-specific 18S-5.8S rDNA internal transcribed spacer region 1 (ITS1) in plankton samples and high throughput sequencing to characterize Pseudo-nitzschia species composition over a decade in Narragansett Bay, including eight years before the 2016-17 closures and two years following. This metabarcoding method can discriminate nearly all known Pseudo-nitzschia species. Several species recur as year-round residents in Narragansett Bay (P. pungens var. pungens, P. americana, P. multiseries, and P. calliantha). Various other species increased in frequency after 2015, and some appeared for the first time during the closure period. Notably, P. australis, a species prevalent in US West Coast HABs and known for high DA production, was not observed in Narragansett Bay until the 2017 closure but has been present in several years after the closures. Annual differences in Pseudo-nitzschia composition were correlated with physical and chemical conditions, predominantly water temperature. The long-term composition trends of Pseudo-nitzschia in Narragansett Bay serve as a baseline for identifying the introduction of new species, understanding shifting assemblages that contributed to the 2016-17 closures, and monitoring species that may be cause for future concern.